Paleosols in the Ruma loess section (Vojvodina, Serbia) - Slobodan B. Marković; Nikola S. Kostić; Eric A. Oches (Revista Mexicana de Ciencias Geológicas)
The Ruma loess section, located in the central part of the south slope of Fruška Gora Mountain, exposes a 20 m thick series of loess and paleosols in the local brickyard. Results of amino acid racemization geochronology confirmed middle- and late-Pleistocene ages of Ruma’s loess-paleosol sequences, and correlates with aminostratigraphic subdivisions at other Central European sites. Paleopedological analyses describe morphology, mineralogy, grain-size distribution and carbonate content of the sediments and paleosols. Five paleosol levels represent the environmental transition from humid forest environments to relatively dry steppe interglacial landscapes during the last about 350 ka. Especially interesting are thick pedogenic layers formed in distinct paleo-depressions, which were created during the last glacial cycle. These horizons provide proxy data useful in the detailed reconstruction of environmental conditions during marine oxygen-isotope stages 5 and 3.